Length-weight relationship and condition factor of three dominant species from the Lake Tasik Kenyir, Terengganu, Malaysia. - Kamaruddin, I. S.; Abdul Satar, Mustafa Kamal; Christianus, Annie; Daud, Siti Khalijah; Nurul Amin, Sanker Mohammad; Yu Abit, L. (Academic Journals, 2011)
The Length-weight Relationship (LWR) and condition factor (K) of three most dominant species from the Tasik Kenyir was evaluated from February 2008 to January 2009. The data were analyzed by the equation of W = aLb and were transferred to Log10W = Log10 a + b Log10 L, for the length-weight relationship and K = W x 100 L-3 for the condition factor. The relative growth coefficient (b) values for Barbodes schwanenfeldii was 2.784, Notopterus sp. was 1.905 and Hampala macrolepidota was at 3.043. The condition factor values varied seasonally for each species that range from 2.48±0.39 to 2.68±0.28 for B. schwanenfeldii, 0.95±0.10 to 1.03±0.20 for Notopterus sp. and from 2.17±0.19 to 2.35±0.39 for H. macrolepidota.